Diagnosis of spotted fever group Rickettsia infections: the Asian perspective. (2019) - Robinson, Matthew T.; Satjanadumrong, Jaruwan; Hughes, Tom; Stenos, John; Blacksell, Stuart D.
Abstract: Spotted fever group rickettsiae (SFG) are a neglected group of bacteria, belonging to the genus Rickettsia, that represent a large number of new and emerging infectious diseases with a worldwide distribution. The diseases are zoonotic and are transmitted by arthropod vectors, mainly ticks, fleas and mites, to hosts such as wild animals. Domesticated animals and humans are accidental hosts. In Asia, local people in endemic areas as well as travellers to these regions are at high risk of infection. In this review we compare SFG molecular and serological diagnostic methods and discuss their limitations. While there is a large range of molecular diagnostics and serological assays, both approaches have limitations and a positive result is dependent on the timing of sample collection. There is an increasing need for less expensive and easy-to-use diagnostic tests. However, despite many tests being available, their lack of suitability for use in resource-limited regions is of concern, as many require technical expertise, expensive equipment and reagents. In addition, many existing diagnostic tests still require rigorous validation in the regions and populations where these tests may be used, in particular to establish coherent and worthwhile cut-offs. It is likely that the best strategy is to use a real-time quantitative polymerase chain reaction (qPCR) and immunofluorescence assay in tandem. If the specimen is collected early enough in the infection there will be no antibodies but there will be a greater chance of a PCR positive result. Conversely, when there are detectable antibodies it is less likely that there will be a positive PCR result. It is therefore extremely important that a complete medical history is provided especially the number of days of fever prior to sample collection. More effort is required to develop and validate SFG diagnostics and those of other rickettsial infections.